2022
DOI: 10.3171/2022.3.spine22197
|View full text |Cite
|
Sign up to set email alerts
|

Association between lower Hounsfield units and proximal junctional kyphosis and failure at the upper thoracic spine

Abstract: OBJECTIVE The aim of this study was to analyze risk factors and avoidance techniques for proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) in the upper thoracic spine with an emphasis on bone mineral density (BMD) as estimated by Hounsfield units (HU). METHODS A retrospective chart review identified patients at least 50 years of age who underwent instrumented fusion extending from the pelvis to an upper instrumented vertebra (UIV) between T1 and T6 and had a preoperative CT, pre- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…1,4 In an effort to reduce the risk of PJK and PJF, many studies have sought to identify risk factors for the development of these complications. 1,[5][6][7][8][9] In their study of patients undergoing thoracolumbar fusions that terminated proximally near the thoracolumbar junction for degenerative indications, Mikula et al 7 identified diminished HU at the UIV as a risk factor for PJK. A subsequent study by the same authors revealed that lower HU at the UIV was also associated with an increased risk of PJK and PJF in patients undergoing long-construct thoracolumbar fusions that terminated proximally in the upper thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4 In an effort to reduce the risk of PJK and PJF, many studies have sought to identify risk factors for the development of these complications. 1,[5][6][7][8][9] In their study of patients undergoing thoracolumbar fusions that terminated proximally near the thoracolumbar junction for degenerative indications, Mikula et al 7 identified diminished HU at the UIV as a risk factor for PJK. A subsequent study by the same authors revealed that lower HU at the UIV was also associated with an increased risk of PJK and PJF in patients undergoing long-construct thoracolumbar fusions that terminated proximally in the upper thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study by the same authors revealed that lower HU at the UIV was also associated with an increased risk of PJK and PJF in patients undergoing long-construct thoracolumbar fusions that terminated proximally in the upper thoracic spine. 8 However, while these studies did consider demographic variables, sagittal alignment parameters, and DEXA measurements in their multivariate analyses, they did not include other potentially important risk factors such as frailty indices and paraspinal fatty degeneration. Consequently, the impact of evidence-based frailty indices and sarcopenia on proximal junctional complications has remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hounsfield unit (HU) obtained from computed tomography (CT) has been widely used for the calculation of bone mineral density (BMD) and the estimation of bone strength. [20][21][22] Moreover, HU measured at a region of interest (ROI) of the screw trajectory presents the approximate BMD and correlates strongly with insertion torque and implant stability in vitro and in vivo studies. [23][24][25][26] Furthermore, Han et al 27 demonstrated that HU values on C2-3 segments indicate a more reliable BMD level than those on C4-7 segments, and HU values of cervical CT provided reliable information regardless of measured sections, age, sex, and degree of degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The Hounsfield unit (HU) obtained from computed tomography (CT) has been widely used for the calculation of bone mineral density (BMD) and the estimation of bone strength [ 20 - 22 ]. Moreover, HU measured at a region of interest (ROI) of the screw trajectory presents the approximate BMD and correlates strongly with insertion torque and implant stability in vitro and in vivo studies [ 23 - 26 ].…”
Section: Introductionmentioning
confidence: 99%